Effects of ultrasonic treatment on accelerating aging of domestic new whiskey in the soaking stage - XU Bin, WU Yu, LV Xuchen, TONG Fenfei, LI Huixing, LUO Jiancheng (Zhongguo niangzao)
To investigate the effect of ultrasonic treatment in the soaking stage on the accelerating aging of new whiskey, the new whiskey was treated with ultrasonic after adding oak chips. Under ice bath conditions, an intermittent treatment method was used with ultrasonic power 720 W, frequency 20 kHz, and ultrasonic treatment for 4 min and stop for 6 min. The treatment lasted for 60 min/d for 7 d. Using the untreated whiskey sample as control, the changes in color, clarity, average cluster particle size, total phenols, oak extract, total esters, and higher alcohol contents of all whiskey samples were measured during the aging, and the differences between whiskey samples aged for 90 d, new whiskey and finished whisky were compared by orthogonal partial least squares-discriminant analysis (OPLS-DA) and rapid sensory analysis. The results showed that compared with the untreated whiskey sample, the color of the whiskey sample treated with ultrasonic increased by 6.4%, and the clarity decreased by 8.9%. The average cluster particle size in the whisky sample was increased in advance by ultrasonic effect, and the contents of syringic acid, vanillic acid, coniferal, coniferyl aldehyde, sinapinaldehyde, and higher alcohols increased in the whiskey sample, while the total ester content decreased. Whiskey samples treated with ultrasonic was closer to the finished whiskey in terms of aroma compared to untreated whiskey samples. Therefore, the ultrasonic treatment of new whiskey could promote the aging of new whiskey in the soaking stage.